Analysis of conjugate Marangoni natural convection in a heating system with an open boundary flow. (November 2022) - Ruvo, Tahmidul Haque; Zisan, HM Toufik Ahmed; Saha, Sumon
Abstract: Marangoni natural convection involved in a heating system with an open boundary layer flow has been numerically analyzed in this article. An isoflux heater is placed below a steel pan (material: AISI 4340 steel) which is partially/fully filled with water to make this model more realistic. The surrounding of this pan has a two-dimensional air domain including a water-air interface. Hence, the air domain has three open boundaries within the computational domain. Conjugate natural convection heat transfer takes place from the solid pan to water and then air, whereas Marangoni convection is facilitated at the water-air interface. Two-dimensional, unsteady Navier-Stokes and energy equations are considered as the governing equations, and those are solved with the help of finite element method. Rayleigh number is varied in the range of laminar regime from 6 × 10 4 to 3 × 10 7 as the governing parameter under different water level conditions. Thermal and flow fields are visualized qualitatively, whereas quantitative distributions of average Nusselt numbers are taken for further analysis. Finally, the exergy of the system is inspected in terms of total entropy generation at individual flow domains. Here, overall heat transfer performance shows a strong dependency on the change of Rayleigh number. Highlights: Two-dimensional open cavity with a bottom isoflux heater is numerically studied Nusselt number in solid-water interface has a minimum with Rayleigh number Average water temperature also shows a minimum with same range of Rayleigh number At higher Rayleigh number, water domain exhibits maximum entropy generation